2022
DOI: 10.1155/2022/5794118
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of the Effect of the Sirtuin Family on Differentiated Thyroid Carcinoma

Abstract: A growing body of experimental evidence suggests that sirtuins (SIRTs) are associated with tumorigenesis in differentiated thyroid cancer (DTC). Nevertheless, the involvement of SIRTs in the pathogenesis of DTC and their clinical value remain ill-defined and should be thoroughly examined. We explored the transcription of SIRTs and survival data of patients with DTC by the systematic utilization of bioinformatics to analyze data of publicly accessible databases including Oncomine, cBioPortal, Kaplan-Meier Plott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…To further investigate the role of KCC2 (SLC12A5) and NKCC1 (SLC12A2) in pan-cancers, we analyzed mutation abundance and frequency of KCC2/NKCC1 in pan-cancer using cBioportal for Cancer Genomics ( ) ( 25 ). A total of 48,834 cancer samples with available DNA variation, including mutations, copy number variation (CNV), somatic number variation (SNV), and profiles from 188 independent curated of non-redundant cohorts were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…To further investigate the role of KCC2 (SLC12A5) and NKCC1 (SLC12A2) in pan-cancers, we analyzed mutation abundance and frequency of KCC2/NKCC1 in pan-cancer using cBioportal for Cancer Genomics ( ) ( 25 ). A total of 48,834 cancer samples with available DNA variation, including mutations, copy number variation (CNV), somatic number variation (SNV), and profiles from 188 independent curated of non-redundant cohorts were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…First, older evidence showed that SIRT3 was highly expressed in DTC compared to benign thyroid tumors, while Wang et al showed that MiR-1225-5p might trigger DTC cell proliferation and metastasis by targeting SIRT3 . Newer findings by Yao and Wang, in a more clinical setting, indicate the opposite, showing that mRNA expression levels of SIRT3 decreased in their DTC model compared to healthy cells and that patients with high SIRT3 expression had a longer disease-free survival …”
Section: Introductionmentioning
confidence: 94%
“…24 Newer findings by Yao and Wang, in a more clinical setting, indicate the opposite, showing that mRNA expression levels of SIRT3 decreased in their DTC model compared to healthy cells and that patients with high SIRT3 expression had a longer disease-free survival. 25 SIRT3 is not only involved in cancer but also in infectious, 26,27 heart, 28 kidney, 29 metabolic, 30,31 and neurodegenerative diseases such as Alzheimer's, Parkinson's, and Huntington's disease, as well as in stroke and traumatic brain injury. 32 A recent study by Yan et al stated that SIRT3 is very likely to play a crucial role in the development of neuropathic pain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A growing body of experimental evidence has implicated SIRTs in the regulation of pivotal cellular processes involved in cancer initiation and progression [ 14 , 15 , 16 , 17 , 106 ]. Although their expression is quite variable among tumor types and may act either as tumor suppressors or promoters depending on the cellular context, some SIRTs have shown clinical relevance with prognostic significance, biomarker potential, and association with drug resistance [ 14 , 15 , 16 , 17 ]. Emerging data have also implicated SIRTs in various aspects of glioma tumorigenesis, including proliferation, apoptosis, autophagy, stemness, angiogenesis, and metastasis, and are discussed in the following sections.…”
Section: Evidence Of Sirts Implication In Gb Pathogenesismentioning
confidence: 99%
“…Eighteen HDACs have been identified thus far and classified into four classes [ 9 ]. Class III HDACs, also known as sirtuins (SIRTs) were originally investigated as potential therapeutic targets in age-related and neurodegenerative diseases [ 10 , 11 ], inflammatory disorders [ 12 ], muscular diseases [ 13 ], and recently, in different cancer types [ 14 , 15 , 16 , 17 ], including GB. The role of SIRTs as regulators of gliomagenesis is currently under thorough research with significant data.…”
Section: Introductionmentioning
confidence: 99%